Avaliação de lagoas de lemnáceas no polimento de esgoto doméstico e produção de biomassa - Garcia, Daiane Cristina de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Stabilization ponds using floating macrophytes, especially duckweeds, have been successfully used for wastewater polishing. This plant use the nutrients (N and P) present in the wastewater for their growth, concentrating them in their biomass and making them available for recovery. Thus, a wastewater treatment plant can work in integrated and sustainable manner, duckweeds can be grown concomitantly with the wastewater treatment. This research aimed to assess the feasibility of tertiary treatment of municipal wastewater integrated the duckweed production. The experiments was conducted in pilot scale, in pond with a volume of 0,44 m 3 , using the stabilization pond effluent from wastewater treatment plant in the municipality of Ilha Solteira-SP for duckweed growth in pond with continuous flow of 0,12 m 3 /day and HRT of 3,8 days. Effluents samples were collected before and after duckweeds ponds, daily analyses (pH, DO and temperature), twice a week (TN, TP and COD) and weekly (total solids, total coliforms and E. coli) were carried out. The duckweeds were harvested with three different frequencies, every 7, 14 and 21 days for quantification of its production. The highest efficiencies of TN, TP, COD and BOD 5 were 74,67%, 66,18%, 88,12% and 91,14%, respectively. E. coli and total coliforms obtained a reduction of 1 log unit. However, the removal efficiencies of total solids were lower, the highest efficiency were 48,90%. Analysis of variance (ANOVA) showed significant differences only for the variables pH, DO, temperature, COD and BOD 5 . The highest duckweeds production rate were harvested every 14 days (5,6 g/m 2 /day dry matter). The assessed treatment system obtained positive results in the reduction of analyzed variables concentrations being an efficient technology with simple operation for domestic wastewater polishing. There have been large variations in duckweed density and production rate, could be associated with effluent ...

Lagoas com macrófitas flutuantes, em especial as lemnáceas, tem sido satisfatoriamente utilizadas para o polimento de esgoto, gerando uma expressiva quantidade de biomassa. Estas plantas utilizam os nutrientes (N e P) presentes no esgoto para o seu desenvolvimento, concentrando-os em sua biomassa e disponibilizando-os para sua recuperação. Desse modo, uma estação de tratamento de esgoto pode trabalhar de forma integrada e sustentável, ou seja, lemnáceas podem ser cultivadas concomitantemente com o tratamento de esgoto. Esta pesquisa teve como objetivo avaliar a viabilidade de tratamento terciário de esgoto doméstico integrado à produção das lemnáceas. O experimento foi realizado em escala piloto, em tanque com volume de 0,44 m 3 , utilizando o efluente de lagoa de estabilização da ETE do município de Ilha Solteira para o seu polimento através de lagoas de lemnáceas em tanque com fluxo contínuo de 0,12 m 3 /dia, e TDH de 3,8 dias. Amostras do efluente foram coletadas antes e após o tratamento em tanque de lemnas, sendo realizadas análises diárias (pH, OD e temperatura), duas vezes por semana (NT, PT e DQO) e semanalmente (ST, DBO 5 , coliformes totais e E. coli). As lemnas foram colhidas em três frequências de colheita diferentes, a cada 7, 14 e 21 dias, para quantificação de sua produção. As maiores eficiências de remoção de NT, PT, DQO e DBO 5 foram de 74, 67%, 66,18%, 88,12% e 91,14%, respectivamente. Para E. coli e coliformes totais observou-se uma redução média de 1 unidade logarítmica. Entretanto, as eficiências de remoção de sólidos totais foram mais baixas, sendo a maior eficiência de 48,90%. A maior taxa de produção foi das lemnas colhidas a cada 14 dias (5,6 g/m 2 /dia de matéria seca). A análise de variância (ANOVA) demonstrou diferença significativa apenas para as variáveis pH, OD, temperatura, DQO e DBO 5 . O sistema de tratamento avaliado obteve resultados positivos na redução da ...
Keywords: Águas residuais - Purificação; Lagoas de estabilização; Biomassa; Sewage -- Purification